Relationship between burnouts, coping strategies and stress management in health care professionals - Rus, Mihaela; Sandu, Mihaela Luminița; Mănescu, Marina Alexandra; Stănescu, Nina (Technium Social Sciences Journal, 2022)
The burnout syndrome is more and more common in scientific research in the country, but also at international level, in different professional categories and hierarchical levels. This research is aimed at medical staff in the Medical-Social Care Unit, nurses and even doctors. A unit established in 2007, which retains the same staff since then, forming a family framework over time, both for employees and beneficiaries, and developing different skills for teamwork. With the pandemic, the rules have become stricter and all staff have been taken out of the comfort zone, which could lead to an imbalance in stress management and put their mark on the emotional state of their employees, thus causing the scholarship. This research covers only one objective, namely the relationship between burnout, cognito-emotional cloning strategies and strategies to manage professional stress, the assumptions being drawn up in turn in the light of the correlation between two variables.